PERANCANGAN SISTEM APLIKASI PENDAFTARAN DAN REKOMENDASI SISWA TELADAN BERBASIS WEB - Vina Devlin (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
School Online Registration and Performance Evaluation System for SMA Poris Indah is a system that provides online registration for new students as well as decision support system for student excel in school. The decision obtained  from student’s scores at school and their achievemets. The system created using Fuzzy Inference System Mamdani to process student’s score and provides the recommendation points for the teacher. From the test result can be known the criteria have its own value and influence. The accumulated samples from each class get the highest point 84.78 and the lowest 68.14.